The Application of Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) in BUMDes MM - Ayu Chairina Laksmi; Defi Tria Amanda (Proceeding International Conference on Accounting and Finance, 2025)
BUMDes (Village-Owned Enterprises) are business entities formed by the village to improve the welfare of village communities. This BUMDes financial report is important for the interests of BUMDes management, village government and village communities. By having transparent and accurate financial reports, BUMDes can monitor financial performance and make better decisions for the sustainability and development of businesses in the village. This research aims to determine the suitability of BUMDes MM's financial reports with the provisions of SAK ETAP. This research uses qualitative methods. The data taken for this research used primary data, namely interviews with the director and treasurer of BUMDes MM and also secondary data with data obtained through the BUMDes MM Treasurer in the form of ready-made financial reports and organizational structures. The results of this research explain that BUMDes MM has not presented financial reports in accordance with SAK ETAP because it only presents profit and loss reports but has not presented balance sheets, cash flow reports, changes in equity reports and notes to financial reports.